HIV/AIDS AND HUMAN SUFFERING: WHERE ON EARTH IS GOD? - Conradie, Ernst M. (Scriptura, 2005)
This article reflects on the classic theodicy problem in relationship with HIV/Aids. It first offers some general comments about the very need to address the theodicy problem. A next section offers an analysis of various sources of human suffering which is then related to an overview of some of the dominant theodicies in current theological discourse. These discussions are brought together in a final section which investigates various possible answers to the question: Where is God amidst the suffering associated with the HIV/Aids pandemic? The article concludes that one of the many challenges that HIV/Aids pose to Christian communities is to offer a plausible account of each aspect of the Christian faith.